IMPLEMENTASI PUBLIC SPEAKING DALAM MENINGKATKAN KEMAMPUAN BERBAHASA ARAB - Zulfa Urwatil Wutsqo; Nuraini Nuraini; Sigit Dwi Laksana (TARBAWI:Journal on Islamic Education, 2020)
This research was conducted with the aim of knowing the implementation of public speaking in improving the arabic language skills of students at Madrasah Diniyah Hidayataul Islam Jetis Ponorogo, knowing the results of the implementation of public speaking in improving the arabic language skills of Madrasah Diniyah Hidaytaul Islam Jetis Ponorogo, and as well as to find the supporting and inhibiting factors of the implementation of public speaking in improving the arabic language skillss of Madrasah Diniyah Hidayatul Islam Jetis Ponorogo. The object of this research is students anad teachers of Madrasah Diniyah Hidayatul Islam Jetis Ponorogo. This research used a qualitative research type. Data collectiontechniques using observation, interviews and documentation. Data were analyzed using conclusion. The research results found in this study are: (1) implementation of public speaking in improving arabic language skills in Madrasah Diniyah Hidayatul Islam Jetis Ponorogo, this activity is designed in muhadhoroh activities, which are carried out once a week with speech method in Arabic language. (2) The results of implementation of public speaking in improving arabic langguage skills in Madarash Diniyah Hidayatul islam Jetis Ponorogo are stuudents who are able to publicly speak in arabic gradually as well addition of their vocabulary.(3)Supporting and inhibiting factors for implementation public speaking in improving Arabic language skill in Madrasah Diniyah Hidayatul Islam Jetis Ponorogo are direct guidance and direction from teachers and friends, and the inhibiting factors is the lack of self confidence and lack of preaparation.